Pengaruh Perbedaan Latar Belakang Pendidikan Remaja Terhadap Kemampuan Membaca al-QurâÄn: Studi Kasus di Desa Mayangan Kecamatan Jogoroto Kabupaten Jombang - Muhsin, Ali; Hidayatulloh, Haris; Abidin, Zainal (DirÄsÄt: Jurnal Manajemen dan Pendidikan Islam, 2017)
There are many religious activities among the villagers of Mayangan, such as the reading of the QurâÄn at mosques held once a month. Generally, its done on Thursday before Friday Legi night and is followed by teens from different educational backgrounds. The purpose of this study is to describe the differences between youth education backgrounds and the capablity to read al-QurâÄn in Murong village. This type of research is quantitative. The research instrument used is documentation, observation, questionnaire and interview. Data analysis using quantitative descriptive method. The population of this study were teenagers in Murong village as many as 150 individuals with a sample of 30% of the population, ie 150 individuals with sampling technique using proportional random sampling. The conclusion of the study is that the capability to read al-QurâÄn = 18,011 + 0,412 for adolescents who have educational background. That is, the educational background is worth 0 (teenagers who do not have educational background), then the reading capability of al-QurâÄn ranges from 18,011.